Virtual Light in the Sports Blackout: An enduring boost of virtual sports or just a temporary respite? - Rogstad, E. T. (idrottsforum.org, 2020)
While the majority of traditional sports events and activities around the world were cancelled, suspended or postponed after the World Health Organization declared a global pandemic, the eSports industry is growing like never before. As one of the greatest benefits of eSports is that it can be played without physical co-location of participants, it offers an engaging distraction for people at home looking for social interaction during times with social distancing. This scholarly commentary draws on existing eSports research literature and relevant news stories in a discussion of what virtual sports can contribute with during a time of crisis when traditional sports are at a standstill, and what challenges virtual sports will have to face in order to make the boost that it is currently experiencing during the pandemic more than just a temporary respite while traditional sporting activities and events are suspended.